2001
DOI: 10.1079/phn200050
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and handgrip strength of older adults in rural Malawi

Abstract: Objective: To examine the relationship between the nutritional status and handgrip strength of older people in rural Malawi. Design: Cross-sectional study. Setting: Lilongwe rural, Malawi, situated approximately 35±50 km from the city. Subjects: Ninety seven males and 199 females participated in this study. Methods: Selected anthropometric measurements were taken and nutrition indices were computed using standard equations. Handgrip strength was measured using an electronic grip strength dynamometer. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
62
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 17 publications
17
62
1
4
Order By: Relevance
“…The results of this study are in agreement with the findings that handgrip strength is positively associated with nutritional status as reported earlier (Guo et al, 1996;Manandhar, 1999;Chilima & Ismail, 2001). Even when controlling for other variables in the regression analysis, poor nutritional status emerged as a significant determinant of handgrip strength in both sexes.…”
Section: Handgrip Strength Related To Nutritional Statussupporting
confidence: 92%
See 4 more Smart Citations
“…The results of this study are in agreement with the findings that handgrip strength is positively associated with nutritional status as reported earlier (Guo et al, 1996;Manandhar, 1999;Chilima & Ismail, 2001). Even when controlling for other variables in the regression analysis, poor nutritional status emerged as a significant determinant of handgrip strength in both sexes.…”
Section: Handgrip Strength Related To Nutritional Statussupporting
confidence: 92%
“…The present study showed poorer performance in older age groups with a more marked decrease above age 70. This is not only in agreement with cross-sectional studies in Malawi and India (Chilima & Ismail, 2001;Manandhar, 1999), but also with Western longitudinal studies that found a significant decline with age in functional performance, and at an accelerating rate at more advanced ages (Kallman et al, 1990;Grimby, 1995).…”
Section: Handgrip Strengthsupporting
confidence: 87%
See 3 more Smart Citations